110k views
2 votes
Which of the following could be values for a, b, and c so that (3x -2)(2x-7) = ax^2 + bx+c?

A. A=6 B=25, C=14 B. A=6 B=-25, C=14

C. A=6 B=-24, C=-14 D. A=5, B=-25, C=-9

2 Answers

2 votes

Answer:

B

Explanation:

Expand the factors and compare coefficients of like terms

(3x - 2)(2x - 7)

= 6x² - 21x - 4x + 14

= 6x² - 25x + 14

Compare coefficients to ax² + bx + c

ax² → 6x² ⇒ a = 6

bx → - 25x ⇒ b = - 25

14 → c ⇒ c = 14

a = 6, b= - 25, c = 14 → B

User Pulsejet
by
4.9k points
3 votes

Answer:

B. A=6 B=-25, C=14

Explanation:

(3x -2)(2x-7)

Using FOIL

= 6x^2 - 21x - 4x + 14

= 6x^2 -25x + 14

So a = 6, b = -25 and c = 14

answer

B. A=6 B=-25, C=14

User Haohaolee
by
4.6k points